2020
DOI: 10.1021/acsomega.9b04005
|View full text |Cite
|
Sign up to set email alerts
|

Gas–Liquid Contactors’ Aeration Capacities When Agitated by Rushton Turbines of Various Diameters

Abstract: Mass transfer processes are one of the most important operations in chemical, biochemical, and food industries worldwide. In the processes that are controlled by the gas−liquid mass transfer rate, the volumetric mass transfer coefficient k L a becomes a crucial quantity. The dataset was measured with the aim to create a correlation for k L a prediction in a non-coalescent batch under the wide range of experimental conditions. The dynamic pressure method, which was reported as physically correct in the past, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The gas dispersion, flow pattern and mixing in bioreactors are all affected by these factors. The gas distribution has a great influence on the dissolved oxygen (DO) content in fermentation broth [ 10 , 11 ]. Shin et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas dispersion, flow pattern and mixing in bioreactors are all affected by these factors. The gas distribution has a great influence on the dissolved oxygen (DO) content in fermentation broth [ 10 , 11 ]. Shin et al .…”
Section: Introductionmentioning
confidence: 99%
“…The gas dispersion, flow pattern and mixing in bioreactors are all affected by these factors. The gas distribution has a great influence on the dissolved oxygen (DO) content in fermentation broth [10,11]. Shin et al indicated that the oxygen supply of fermentation broth, which was the restrictive factor for enzyme production by Aspergillus oryzae, was affected by impeller geometries [12].…”
mentioning
confidence: 99%